The Impact of Food Import Dependency on the Performance and Growth of Agro-Processing Firms in the Gambia - Darry, Madiba (My University, 2026)
This study investigates the structural challenges and adaptive strategies of the agro- processing firms in The Gambia, with a concentration on import dependency, market competition, and policy-related constraints. In promoting food security, employment, and economic diversification in many developing economies, the agro-processing sector plays a very important role. However, the performance of these agro-processing sectors is often shaped by broader structural and institutional factors. This research analyses three agro-processing firms using a qualitative case study approach. The firms include the National Food Security, Processing and Marketing Corporation (SAARO), Gambia Horticultural Enterprise (GHE), and AK Agro Development Enterprise. The method of data collection was through interviews, which helps in understanding firm-level observations and also the production systems, sourcing strategies, and market engagement. To understand common patterns and specific responses to external pressures by the firms, a cross-case analytical framework was employed. The findings reveal that a large number of agro-processing firms in The Gambia operate under significant structural constraints. These constraints are primarily driven by high dependence on imported machinery, inputs, and packing materials. Additionally, firms face strong competition from imported processed goods, which benefit from economies of scale, advanced technologies, and strong branding. Given these conditions, it limits the competitiveness and growth potential of domestic agro-processing enterprises. Despite these challenges, the study finds that firms adopt a range of strategies in order to sustain operations. These strategies include vertical integration, decentralised sourcing, export orientation, and supply chain coordination. However, although these strategies are very effective, they remain insufficient to overcome systemic barriers such as weak infrastructure, limited access to finance, regulatory inefficiencies, and shifting consumer preferences towards imported products. The study concludes that structural and policy-related issues beyond firm-level control significantly affect the performance of agro-processing companies in The Gambia. The industry has a lot of potential for economic growth, but ongoing institutional and market 7 obstacles prevent it from growing. The results offer a foundation for further study and policy discussion while also deepening our understanding of the dynamics of agro-processing in countries that rely heavily on imports.